Socioeconomic disadvantage increases risk of prevalent and persistent depression in later life - Almeida, O.; Pirkis, J.; Kerse, N.; Sim, M.; Flicker, L.; Snowdon, J.; Draper, B.; Byrne, G.; Lautenschlager, N.; Stocks, N.; Alfonso, Helman; Pfaff, J. (2012)
Background: Depression is more frequent in socioeconomically disadvantaged than affluent neighbourhoods, but this association may be due to confounding. This study aimed to determine the independent association between socioeconomic disadvantage and depression. Methods: We recruited 21,417 older adults via their general practitioners (GPs) and used the Patient Health Questionnaire (PHQ-9) to assess clinically significant depression (PHQ-9 = 10) and major depressive symptoms. We divided the Index of Relative Socioeconomic Disadvantage into quintiles. Other measures included age, gender, place of birth, marital status, physical activity, smoking, alcohol use, height and weight, living arrangements, early life adversity, financial strain, number of medical conditions, and education of treating GPs about depression and self-harm behaviour. After 2 years participants completed the PHQ-9 and reported their use of antidepressants and health services. Results: Depression affected 6% and 10% of participants in the least and the most disadvantaged quintiles. The proportion of participants with major depressive symptoms was 2% and 4%. The adjusted odds of depression and major depression were 1.4 (95% confidence interval, 95%CI = 1.1-1.6) and 1.8 (95%CI = 1.3-2.5) for the most disadvantaged. The adjusted odds of persistent major depression were 2.4 (95%CI = 1.3-4.5) for the most disadvantaged group. There was no association between disadvantage and service use. Antidepressant use was greatest in the most disadvantaged groups. Conclusions: The higher prevalence and persistence of depression amongst disadvantaged older adults cannot be easily explained by confounding. Management of depression in disadvantaged areas may need to extend beyond traditional medical and psychological approaches. © 2012 Elsevier B.V. All rights reserved.